Rickettsia parkeri: A Rickettsial pathogen transmitted by ticks in endemic areas for spotted fever rickettsiosis in southern Uruguay - Venzal, José M. (2012)
At first Rickettsia conorii was implicated as the causative agent of spotted fever in Uruguay diagnosed by serological assays. Later Rickettsia parkeri was detected in human-biting Amblyomma triste ticks using molecular tests. The natural vector of R. conorii, Rhipicephalus sanguineus, has not been studied for the presence of rickettsial organisms in Uruguay. To address this question, 180 R. sanguineus from dogs and 245 A. triste from vegetation (flagging) collected in three endemic localities were screened for spotted fever group (SFG) rickettsiosis in southern Uruguay. Tick extracted DNA pools were subjected to PCR using primers which amplify a fragment of the rickettsial gltA gene. Positive tick DNA pools with these primers were subjected to a second PCR round with primers targeting a fragment of the ompA gene, which is only present in SFG rickettsiae. No rickettsial DNA was detected in R. sanguineus. However, DNA pools of A. triste were found to be positive for a rickettsial organism in two of the three localities, with prevalences of 11.8% to 37.5% positive pools. DNA sequences generated from these PCR-positive ticks corresponded to R. parkeri. These findings, joint with the aggressiveness shown by A. triste towards humans, support previous data on the involvement of A. triste as vector of human infections caused by R. parkeri in Uruguay.